Landslide susceptibility mapping based on the coupling of two correlation methods and the BP neural network model: A case study of the Baihetan Reservoir area, China - Xue, Zhenghai; Feng, Wenkai; Li, Botao; Zhou, Yongjian; Yi, Xiaoyu; Wu, Mingtang (Frontiers in Environmental Science, 2022)
The correlation calculation model between landslide and mapping factors has a direct influence on the accuracy of landslide susceptibility mapping results. Using the Baihetan reservoir area as a case study, the effect of several correlation models on mapping landslide susceptibility is studied. The frequency ratio (FR) and the information value (IV) coupled BP neural network (BPNN) model was utilized to assess landslide susceptibility, with the mapping results of the single BPNN model acting as a reference. The ROC curve, the frequency ratio, and the susceptibility index distribution (mean value and standard deviation) are used to compare and assess landslide susceptibility values. The FR-BPNN coupling model is less precise than the IV-BPNN model. Findings from a single BPNN model for susceptibility mapping are less exact than those from a coupled model. Using the coupling model of the mapping factor correlation approach to assess landslide susceptibility has evident benefits, according to the study. The coupled model employing IV as the correlation method provides the most accurate and dependable susceptibility findings, and the mapping results are more consistent with the actual distribution of landslides in the study area. It can effectively direct disaster prevention efforts in the reservoir region.